Representasi Bahasa Generasi Z pada Konten Kreator Fujian Utami Putri di Media Sosial - Adinda Atiqotuz Zummah; Magfirotul Hamdiah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to describe the form and sociolinguistic function of Generation Z language representation used by content creator Fujianti Utami Putri on social media. A descriptive qualitative approach with content analysis method was applied to dissect this linguistic phenomenon deeply. The data source consists of an audio-visual document from a single video titled "Mau ketemu bayiiiii" (2026), lasting 1 minute and 53 seconds, downloaded from the official TikTok account @fujiiian. The research data includes words, phrases, and sentences in oral utterances as well as on-screen text that contain the linguistic characteristics of the younger generation. Data collection used the observation method through the Uninvolved Conversation Observation Technique (SBLC) and note-taking technique. Data analysis was completed through data reduction, data display in matrix tables, contextual interpretation, and conclusion drawing. The results show 12 data units classified into four main categories: first, English code-switching (stress relief, glowing, glass skin), second, regional dialects adapted into national slang (sat-set and ruwet), third, creative affixation neologisms (ngonten), and fourth, hyperbolic dictions (mantul). Functionally, this hybrid language variety acts as a strategic sociolinguistic instrument to strengthen the collective identity among Generation Z while breaking down formality barriers between a public figure and the audience to build emotional intimacy. This phenomenon proves that the Indonesian language is a living entity that continues to evolve creatively amidst digital technology disruption.